TREND AND DETERMINANTS OF CSR DISCLOSURE IN INDONESIA: A RESPONSE OF THE ACT NO. 40 (2007) - Cahyonowati, Nur; -, Darsono (Jurnal Dinamika Akuntansi, 2013)
This study aims to examine the trend of corporate social responsibility disclosure in Indonesia with regard to the Act No. 40 (2007). Mandatory corporate social responsibility has been debated among businessmen in Indonesia. This research proposes important suggestions to achieve effective implementation of the act. In addition, ÃÂ this study aims to identify determinants of corporate social responsibility (CSR) disclosure among companies listed on Indonesia Stock Exchange. This study uses content analysis on five year annual reports to measure the level of corporate social responsibility disclosure. To examine the trend of disclosure, the study requires complete annual reports during observed period. This study found the increase of trend in corporate social disclosure during observed period. However, the increase was not significant indicated by low response of companies to the act. The results of content analysis indicate that human resources or employee topic dominate CSR disclosure. Regarding to the quantity of disclosure, the study found that 55,9% of disclosures were written in paragraph which less than half of A4 size paper. The study also found that 71% of disclosures was in non-monetary term. The results of regression analysis indicate that firm size is a pivotal determinant of CSR but not for profitability and public ownership. However, these findings are lack of generalization due to small sample size.